Implementation of the goal-setting components in popular physical activity apps: Review and content analysis. (July 2019) - Baretta, Dario; Bondaronek, Paulina; Direito, Artur; Steca, Patrizia
Objective: Goal setting is an effective strategy to promote physical activity. Commercial apps that tackle physical activity often include goal setting; however, it is unknown whether the implementation of the goal-setting components is congruent with the theory. This study evaluated the quality of goal setting in popular free and paid physical activity apps by assessing the presence of effective goal-setting components. Methods: A six-item scale was developed based on the goal-setting literature and used for coding each app for the presence/absence of goal-setting components (i.e. specificity, difficulty, action planning, timeframe, goal evaluation and goal re-evaluation). Cohen's Kappa was used to evaluate inter-rater reliability for each scale item. The number of goal-setting components included in the 40 apps was calculated and the difference between free and paid apps was assessed. Results: All scale items achieved satisfactory inter-rater reliability except 'goal evaluation'. The most frequently included goal-setting components in popular physical activity apps were 'goal specificity' (95% of the apps) and 'goal timeframe' (67.5%). Conversely, only 47.5% and 25% of the apps implemented 'action planning' and 'goal difficulty', respectively, and none included 'goal re-evaluation'. No differences emerged between free and paid apps. Conclusions: The quality of the goal-setting strategy in popular physical activity apps could be improved by introducing components scarcely implemented to date. In particular, tailoring the goal difficulty to the users' ability level and re-evaluating the goals based on achievements should be implemented to increase the quality of goal setting.